Blanket NOP rules and regional realities: from the field. (27th December 2022) - Miller, Emily M.; Hendrickson, Mary; Murakami, Christopher; Clark, Kerry
Abstract: There are fewer Certified Organic producers in the Mid-South US (southern half of Missouri, western Kentucky and Tennessee, northern Arkansas and eastern Oklahoma) than in other regions of the country such as the Upper Midwest, West Coast, or Northeastern US. Taus et al . (2013) The Professional Geographer 65, 87–102, posit that these clusters suggest regional characteristics impact adoption of organic agriculture and admit that regional studies lack consensus on the role of factors that drive adoption. This paper seeks to understand if there are regionally distinct challenges and opportunities for organic production in the region. Fourteen certified organic producers in Missouri were interviewed and areas of challenges and opportunities specific to their certification were identified within the three a priori themes of (1) biophysical characteristics, (2) marketing infrastructure and (3) financial feasibility. We suggest directions for future policy support from the National Organic Program (NOP) and bolstered feedback structures within the National Organic Standards Board to address regional disparities.